Factors influencing retention in care after starting antiretroviral therapy in a rural South African programme. - Tom H Boyles (Public Library of Science (PLoS), 2011)
Introduction The prognosis of patients with HIV in Africa has improved with the widespread use of antiretroviral therapy (ART) but these successes are threatened by low rates of long-term retention in care. There are limited data on predictors of retention in care, particularly from rural sites. Methods Prospective cohort analysis of outcome measures in adults from a rural HIV care programme in Madwaleni, Eastern Cape, South Africa. The ART programme operates from Madwaleni hospital and seven primary care feeder clinics with full integration between inpatient and outpatient services. Outreach workers conducted home visits for defaulters. Results 1803 adults initiated ART from June 2005 to May 2009. At the end of the study period 82.4% were in active care or had transferred elsewhere, 11.1% had died and 6.5% were lost to follow-up (LTFU). Independent predictors associated with an increased risk of LTFU were CD4 nadir >200, initiating ART as an inpatient or while pregnant, and younger age, while being in care for >6 months before initiating ART was associated with a reduced risk. Independent factors associated with an increased risk of mortality were baseline CD4 count <50 and initiating ART as an inpatient, while being in care for >6 months before initiating ART and initiating ART while pregnant were associated with a reduced risk. Conclusions Serving a socioeconomically deprived rural population is not a barrier to successful ART delivery. Patients initiating ART while pregnant and inpatients may require additional counselling and support to reduce LTFU. Providing HIV care for patients not yet eligible for ART may be protective against being LTFU and dying after ART initiation.